The Sidoarjo District Health Office's Strategy in Dealing with Stunting - Rodiyah, Isnaini; Abadi, Totok; Sari, Risa (Indonesian Journal Publisher, 2022)
Stunting or malnutrition is a condition of toddlers who cannot grow properly due to malnutrition in their bodies which causes children to not be able to develop according to their age. This research is to find out how the Sidoarjo Regency Health Office's strategy in dealing with stunting cases that occur in Sidoarjo Regency today. This research methodology is descriptive qualitative. The type of data used in this research is qualitative. Data collection techniques are carried out by means of interviews, online data searches, documentation and observation. This study shows that the strategy of the Sidoarjo district health office in dealing with stunting cases has not been as expected, this is due to the lack of public awareness of stunting, and the community lacks understanding about stunting. village governments need to carry out stunting prevention activities by implementing the Healthy Living Community Movement through nutrition improvement training.